Proximisation, metaphor and threat in experiences of insect and bug phobias - Olivia Knapton (Language and Health)
Animal phobias are a relatively common type of phobia yet are often overlooked in qualitative research into mental health and illness. This study uses discourse analysis informed by cognitive linguistics to investigate people’s experiences of a specific kind of animal phobia, that of insects and other bugs. Through an analysis of proximisation and metaphor in interviews with 27 women with these phobias, this study shows how the feared bugs are conceptualised as an outsider threat that continually encroaches upon the deictic centre of the self or the home. The narrowing of the space between the bug and the deictic centre is at once literal (i.e. the bug moves towards the self) and metaphorical, that is, the bug is conceptualised as an agent with the wilful intent to perform deliberate acts of harm on the deictic centre. The findings are discussed in relation to several socially-situated issues, namely: the nature of disgust, women’s experiences of vulnerability and violence, and the meanings created for insects and bugs through anthropomorphic discursive representations.